The European core-periphery divide: towards a new narrative - Sara Casagrande; Bruno Dallago (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2023)
Economic theory has recently begun to consider the economic impact of narratives. Narrative economics can also be extended to the analysis of the economic-political effect of narratives in the context of the European core-periphery divide, which intensified after the European sovereign-debt crisis. The dominant narrative of the crisis has placed a lot of responsibility on southern member countries. With the outbreak of the COVID-19 emergency, this narrative has returned to influence European public debate. The authors state the importance of analysing the dominant narrative to understand its validity in explaining the sovereign-debt crisis, and the importance of overcoming it to face the health emergency effectively. Therefore, starting from some alternative explanations regarding the European crisis, a new alternative narrative is presented, which underlines the issues connected to the competitive attitude among member countries and the political disequilibrium that characterizes Economic and Monetary Union architecture.
Keywords: F15; O52; P16; 330; austerity; core and periphery countries; economic integration; European sovereign-debt crisis; eurozone; financial deregulation; fiscal discipline; fiscal policy; foreign debt; narrative economics; politics; privatizations